Concealing Robots in Environments: Enhancing Navigation and Privacy through Stealth Integration - Hoorfar, Hamid; Kosarirad, Houman; Taheri, Nedasadat; Fathi, Faraneh; Bagheri, Alireza (EAI Endorsed Transactions on AI and Robotics, 2023)
With the continuous advancement of robotics technology, the integration of robots into diverse human environments has become increasingly prevalent. However, the presence of robots in public spaces can often elicit discomfort or unease among individuals. To address this concern, the concept of concealing robots in various settings has emerged as an innovative approach to improve robot navigation and interaction while minimizing intrusion on human privacy. This paper explores the motivations, challenges, and potential benefits of hiding robots in different environments, particularly within the context of swarm robotics where multiple interconnected robots form a cohesive swarm. Equipped with onboard processing, communication, and sensing capabilities, these robots can autonomously interact with each other and adapt to the environment.The paper investigates the problem of maximizing the number of hidden orthogonal swarm robots, considering scenarios in which robots need to navigate and operate within polygonal environments. Specifically, it presents a 4-approximation algorithm for computing a maximum hidden robot set in such environments. The algorithm offers a practical solution for determining an efficient arrangement of robots that minimizes their visibility while ensuring effective swarm operation.By concealing robots in diverse environments, several benefits can be achieved. First, it helps to alleviate discomfort or unease among individuals, allowing for smoother integration of robots into public spaces. Additionally, concealing robots enhances their navigation capabilities by leveraging stealth techniques, allowing them to move seamlessly and unobtrusively within the environment. This approach also promotes improved human-robot interaction, as the reduced visibility of the robots can alleviate concerns and foster a more natural and comfortable interaction between humans and robots. The paper sheds light on the current state of the field, discussing the motivations behind concealing robots in different settings and highlighting the challenges that need to be addressed. Furthermore, it presents insights into future directions, including the development of more advanced stealth technologies, ethical frameworks for integrating hidden robots, and the potential impact on urban planning and infrastructure. In conclusion, hiding robots in diverse environments offers a promising approach to enhancing robot navigation, interaction, and privacy. The research presented in this paper contributes to the understanding of this emerging field and provides a foundation for further exploration and development of hiding strategies for swarm robotics in various settings.
Keywords: Swarm robotics; Robot navigation; Maximum hidden set; Path planning; Human-robot interaction; Stealth technology